2010
DOI: 10.1007/s11695-010-0160-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Pyramid for Post-gastric Bypass Patients

Abstract: The development of educational tools that are easy to understand and follow is essential for effective patient management during the surgery follow-up period. The pyramid can be used as a tool to help both therapists and patients to understand nutrition recommendations and thus promote a healthy long-term post-op dietary pattern based on high-quality protein, balanced with nutrient-dense complex carbohydrates and healthy sources of essential fatty acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
3
41

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 45 publications
4
85
3
41
Order By: Relevance
“…There are currently no studies that address changes in colorectal mucosal proliferation state or inflammation after gastroplasty or gastric banding, but a unifying hypothesis is that each of the obesity surgery procedures could lead to the promotion of colorectal carcinogenesis via altered colorectal metabolite profiles, secondary to changes to the gut microbiota, combined with modified dietary intake postoperatively. [28][29][30] For example, a diet high in protein is one of the cornerstones of postoperative nutritional care, 31,32 but it has recently been shown that a high-protein, low-carbohydrate diet can promote detrimental metabolite profiles in the colorectum, including a decrease in short-chain fatty acid concentrations and increased exposure to N-nitroso compounds, both of which have been implicated in driving colorectal carcinogenesis. 33 Recently, it has been reported that alterations in the intestinal microbiota and fecal metabolite profile after Roux-en-Y gastric bypass in a rat model are associated with increased fecal cytotoxicity compatible with increased carcinogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no studies that address changes in colorectal mucosal proliferation state or inflammation after gastroplasty or gastric banding, but a unifying hypothesis is that each of the obesity surgery procedures could lead to the promotion of colorectal carcinogenesis via altered colorectal metabolite profiles, secondary to changes to the gut microbiota, combined with modified dietary intake postoperatively. [28][29][30] For example, a diet high in protein is one of the cornerstones of postoperative nutritional care, 31,32 but it has recently been shown that a high-protein, low-carbohydrate diet can promote detrimental metabolite profiles in the colorectum, including a decrease in short-chain fatty acid concentrations and increased exposure to N-nitroso compounds, both of which have been implicated in driving colorectal carcinogenesis. 33 Recently, it has been reported that alterations in the intestinal microbiota and fecal metabolite profile after Roux-en-Y gastric bypass in a rat model are associated with increased fecal cytotoxicity compatible with increased carcinogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Patients should be repeatedly educated about staged meal progression dependent on the time elapsed after surgery and based on the type of surgical procedure they underwent (EL A, B, C, D [177][178][179][180][181][182][183][184][185] ). Patients should also be informed that an excessive number and size of meals will probably result in lower weight loss.…”
Section: Follow-upmentioning
confidence: 99%
“…70,71 RYGB surgery leads to substantial changes in the neural response to food cues, and the importance of this in future research and outcome-based studies is paramount to the long-term success of metabolic surgery. 72 The presence of H. pylori, as part of chronic active gastritis, on preoperative endoscopy, has been documented in 85.5% of patients, in a study on morbidly obese Saudi patients undergoing bariatric surgery.…”
Section: Aspiration Pneumonia 1 Pneumoniamentioning
confidence: 99%